2‐Phenoxy‐nicotinamides are Potent Agonists at the Bile Acid Receptor GPBAR1 (TGR5). Issue 4 (7th December 2012) - Martin, Rainer E.; Bissantz, Caterina; Gavelle, Olivier; Kuratli, Christoph; Dehmlow, Henrietta; Richter, Hans G. F.; Obst Sander, Ulrike; Erickson, Shawn D.; Kim, Kyungjin; Pietranico‐Cole, Sherrie Lynn; Alvarez‐Sánchez, Rubén; Ullmer, Christoph
<x xml:space="preserve">Abstract</x> Potency with potential: 2‐Phenoxy‐ nicotinamides were identified as potent agonists at the GPBAR1 receptor, a target in the treatment of obesity, type 2 diabetes and metabolic syndrome. Extensive structure–activity relationship studies supported by homology modeling and docking resulted in the identification of optimized GPBAR1 agonists, potent against both human and mouse receptors, endowed with favorable physicochemical properties and good metabolic stability.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>